An investigation into the relationship between social media addiction and emotional eating behaviour of university students - Akdeniz, Hakan; Taş, Burak; Koçoğlu, Behçet; Toprak, Pınar Yağmur (Progress in Nutrition, 2022)
Background and aim: The purpose of this study was to investigate the relationship between social media use and emotional eating behaviour. Method:  The sample of the study was comprised of 301 students consisting of 153 male and 148 female students, studying at the Faculty of Sport Sciences at Kocaeli University. The "Social Media Addiction Scale" developed by Sahin and Yagci (2017) and the "Emotional Eating Scale" developed by Bilgen (2018) were used to obtain data in the study. The descriptive characteristics of the students participating in the study were determined using frequency and percentage analyses. Skewness and Kurtosis values were checked to see if the data had a normal distribution. While correlation analysis was used to determine the relationship between the study variables, regression analysis was used to determine the effect. Results: The social media addiction scale and the emotional eating scale were found to have a positive and significant relationship (p